Serum Copper and Zinc levels among Iranian vitiligo patients - Zahra Khoshdel; Naser Gholijani; Maryam Niknam; Nasim Rahmani; Mohsen Hemmati-Dinarvand; Fakhraddin Naghibalhossaini (Mattioli1885, 2022)
Introduction: Vitiligo is a chronic skin disease, which its etiopathogenesis is not fully understood. Numerous studies have suggested that oxidative stress may play a role in the pathophysiology of vitiligo. There are controversial reports as to the changes of serum trace elements, copper and zinc levels in vitiligo patients. Objective: In this study, we evaluated the alterations in the level of serum Cu and Zn among a group of Iranian vitiligo patients. Methods: The levels of serum Cu and Zn were compared between 117 vitiligo patients and 137 healthy controls using atomic absorption spectrophotometry. Results: The mean Cu and Zn levels in the case group (113.57 ± 59.43 and 95.01 ± 58.95 μg/dl, respectively) were significantly lower than those of the control group (138.90 ± 38.14 and 121.83 ± 33.80 μg/dl, respectively) (p= 0.00). We also observed significantly lower serum Cu and Zn concentrations in young (<50 years) than the elderly (≥50 years) patients (p=0.00). The mean Cu and Zn levels in the patients with generalized vitiligo (111.63±54.18 and 93.11±59.33 μg/dl, respectively) were significantly lower than patients with localized vitiligo (120.74 ±71.64 and 98.69±58.63 μg/dl, respectively) and those in the control group (p = 0.00). The serum Cu/Zn ratio obtained in the young and male patients was higher than those in their matched control counterparts (p=0.01). Conclusions: The current study has shown that the disturbance of serum Cu and Zn levels is associated with vitiligo, and may play an important role in the disease development of Iranian vitiligo patients.